Texas law review ([Texas Law Review Association], 1922)
A "Bar Association number" issued annually in Oct.; in v. 1-18, this no. contains Proceedings of the 42nd-59th annual sessions, 1923-1940 of the Texas Bar Association; in v. 18-26 contains Proceedings of the 1st-9th annual meetings, 1940-1948 of the State Bar of Texas.